2016
DOI: 10.1186/s12967-016-1075-6
|View full text |Cite
|
Sign up to set email alerts
|

FGFR1 and NTRK3 actionable alterations in “Wild-Type” gastrointestinal stromal tumors

Abstract: BackgroundAbout 10–15% of adult, and most pediatric, gastrointestinal stromal tumors (GIST) lack mutations in KIT, PDGFRA, SDHx, or RAS pathway components (KRAS, BRAF, NF1). The identification of additional mutated genes in this rare subset of tumors can have important clinical benefit to identify altered biological pathways and select targeted therapies.MethodsWe performed comprehensive genomic profiling (CGP) for coding regions in more than 300 cancer-related genes of 186 GISTs to assess for their somatic al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
187
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 184 publications
(200 citation statements)
references
References 47 publications
3
187
0
10
Order By: Relevance
“…Recently, we and others reported a handful of gene fusions in GIST 47 (Table 1). However, here we report a novel, previously unreported PRKAR1B-BRAF gene fusion in a patient with GIST (Figure 2).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, we and others reported a handful of gene fusions in GIST 47 (Table 1). However, here we report a novel, previously unreported PRKAR1B-BRAF gene fusion in a patient with GIST (Figure 2).…”
Section: Discussionmentioning
confidence: 97%
“…3 We and others recently reported that a small subset of GISTs also occur due to kinase fusions (eg, ETV6-NTRK3 , FGFR1-TACC1 , FGFR1-HOOK3 ), a previously unappreciated mechanism for GIST tumorigenesis. 47 …”
mentioning
confidence: 99%
“…We gathered SDHA VUS from two primary sources: The OHSU Knight Diagnostics Laboratory (Portland, OR) and the literature(12,13). The majority of the variants pulled from the literature were found in a review highlighting the need for a functional model to characterize SDHx variants of unknown significance (12).…”
Section: Methodsmentioning
confidence: 99%
“…The majority of the variants pulled from the literature were found in a review highlighting the need for a functional model to characterize SDHx variants of unknown significance (12). The remaining literature variants are from a paper identifying novel causes of GIST that were WT for any known oncogenic driver of GIST (13). A collaboration with the OHSU Knight Diagnostics Laboratory, which offers a targeted exome panel to identify genetic drivers in GIST which includes all four SDHx subunits (https://www.ohsu.edu/custom/knight-diagnostic-labs/home/test-details?id=GeneTrails+GIST+Genotyping+Panel), lead to identification of several novel variants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation